STRATEGI ZALORA INDONESIA MENGELOLA BISNIS FESYEN DI TENGAH PANDEMI - Susi Hartanto (Jurnal Imagine, 2021)
Zalora strategies in the midst of pandemic are: 1) Expand 4 shopping categories (health & beauty, kids, luxury, home) and adding brands and network to 2 existing categories (fashion and sports); 2)Actively hold marketing campaign, especially related to tik-tok influencers and other online media, and keep maintain a small portion of offline campaigns; 3) Adding shopping features for customers in both desktop and mobile app versions; 4) Providing ease, rewards, and cashback for marketplace brands (there are 2 brand categories in Zalora Indonesia: catalog and marketplace, where marketplace holds a bigger percentage); 5) Empowering data-driven decisions for suppliers through Trender platform. From Zalora Indonesia internal data, this article is expected to provide useful information for fashion enthusiasts or academics about newest update in Indonesia fashion industry.